Anticancer Activity of Astaxanthin-Incorporated Chitosan Nanoparticles - Eun Ju Hwang; Young-IL Jeong; Kyong-Je Lee; Young-Bob Yu; Seung-Ho Ohk; Sook-Young Lee (Molecules, 2024)
Astaxanthin (AST)-encapsulated nanoparticles were fabricated using glycol chitosan (Chito) through electrostatic interaction (abbreviated as ChitoAST) to solve the aqueous solubility of astaxanthin and improve its biological activity. AST was dissolved in organic solvents and then mixed with chitosan solution, followed by a dialysis procedure. All formulations of ChitoAST nanoparticles showed small diameters (less than 400 nm) with monomodal distributions. Analysis with Fourier transform infrared (FT-IR) spectroscopy confirmed the specific peaks of AST and Chito. Furthermore, ChitoAST nanoparticles were formed through electrostatic interactions between Chito and AST. In addition, ChitoAST nanoparticles showed superior antioxidant activity, as good as AST itself; the half maximal radical scavenging concentrations (RC50) of AST and ChitoAST nanoparticles were 11.8 and 29.3 µg/mL, respectively. In vitro, AST and ChitoAST nanoparticles at 10 and 20 µg/mL properly inhibited the production of intracellular reactive oxygen species (ROSs), nitric oxide (NO), and inducible nitric oxide synthase (iNOS). ChitoAST nanoparticles had no significant cytotoxicity against RAW264.7 cells or B16F10 melanoma cells, whereas AST and ChitoAST nanoparticles inhibited the growth of cancer cells. Furthermore, AST itself and ChitoAST nanoparticles (20 µg/mL) efficiently inhibited the migration of cancer cells in a wound healing assay. An in vivo study using mice and a pulmonary metastasis model showed that ChitoAST nanoparticles were efficiently delivered to a lung with B16F10 cell metastasis; i.e., fluorescence intensity in the lung was significantly higher than in other organs. We suggest that ChitoAST nanoparticles are promising candidates for antioxidative and anticancer therapies of B16F10 cells.